Synthesis and properties of Layered Organic–inorganic Hybrid Material: Zn-Al Layered Double Hydroxide–dioctyl Sulfosuccinate Nanocomposite - Hussein, Mohd Zobir; Hwa, Tan Kim (Springer, 2000)
A layered organic-inorganic hybrid nanocomposite was prepared by using a surfactant, dioctyl sulphosuccinate (DSS) as a guest in Zn-Al layered double hydroxide (LDH) inorganic host by a self-assembly technique. The ZnAl ratio of the mother liquor was kept constant at 4 at the beginning of the synthesis. Powder X-ray diffractogram shows that the basal spacing of the Zn-Al LDH with sulphate as the intergallery anion (ZASUL) expanded from 11.0 to 26.3 Å to accommodate the DSS surfactant anion for the formation of the Zn-Al LDH-DSS layered organicinorganic hybrid nanocomposite (ZADON). It was also found that the BET surface area reduced by about 90%, from 22.5 to 2.2 m2/g, for ZASUL and ZADON, respectively if 0. 1 M DSS was used for the synthesis of the latter.